Description of production system and on-farm phenotypic characterization of Central Highland and Woyto-Guji goat breeds in Ethiopia - Zergaw, N.; Dessie, Tadelle; Kebede, K. (Cambridge University Press, 2016)
The study examines phenotypic characterization of Central Highland and Woyto-Guji goat breeds at Meta Robi and Konso districts of Ethiopia. Purposive and random sampling techniques were employed to select sample villages and respondent. For administration of semi-structured questionnaire and phenotypic characterization, a total of 240 households and 601 adult animals, respectively, were selected. The average goat flock size (31.25 ± 22.46) owned per household of Konso was significantly (P < 0.01) higher than Meta Robi (12.73 ± 8). In Konso, natural pasture was the most frequently mentioned feed source during wet season, while hay was the most important feed source during dry season. On the other hand, in Meta Robi, natural pasture was the most frequently mentioned feed source during wet and dry seasons. Coat colour type, horn shape, ear orientation, wattle and beard were found to differ highly significantly (P < 0.001) among the two goat breeds. Goat breed had a significant effect (P < 0.001) on body weight and other body measurements except pelvic width (P > 0.05). The least-square means of body weight, body length, height at wither, chest girth, chest width, ramp length, horn length, ear length and pelvic width of Central Highland female goats were 29.5 ± 0.2 kg, 62.2 ± 0.2 cm, 67.5 ± 0.2 cm, 72.9 ± 0.2 cm, 13.4 ± 0.1 cm, 19.7 ± 0.1 cm, 12.8 ± 0.2 cm, 14.6 ± 0.1 cm and 13.5 ± 0.1 cm, respectively. The corresponding values for Woyto-Guji female goats were 24.8 ± 0.3 kg, 57.4 ± 0.2 cm, 61.9 ± 0.2 cm, 68.3 ± 0.2 cm, 12.1 ± 0.1 cm, 17.3 ± 0.1 cm, 10 ± 0.2 cm, 13 ± 0.1 cm and 13.4 ± 0.1 cm, respectively. The observed variations in production system and morphological traits among the sample populations coupled with their adaptive traits would indeed justify the need for designing breed improvement programme for both breeds.